CONTRIBUTION OF THE TEACHER'S COMPETENCE AND THE STUDENT'S EMOTIONAL QUOTIENT TOWARD THE ACHIEVEMENT ON BIOLOGY OF THE STUDENT OF SMUN 2 SUKOHARJO IN ACADEMIC YEAR OF 2OO4l2005 - SUMANTO SUMANTO; Sri Widoretno; LAELY TRI ASTUTI (Bioedukasi: Jurnal Pendidikan Biologi, 2005)
The purposes of this research were to find out the contribution of the teacher's competence and Students' emotional iquotient toward the achievement on biolog of the student of SMU Negeri 2 Sukoharjo in theacademic year of 2004/2005.The study carried out by descriptive quantilative method. 'the population of the study was all students of the second grade in SMA Negeri 2 Sukoharjo, in the academic year of 2004/2005. The sampling technique used in the sludy was random sampling. The techniques usedfor collecling data were questionaire and documentation technique. The data were then analized by regression analysis.Considering upon the results, the research concluded that there were significant contribution of the: (I) Teachers' competence to biological learning achievment (r,ry : 0,450 at the level of significance S%o); (2) Sludenls'emotional quotient to biological learning achievement (re, = 0,410.at the level of significance 5%o); (3) Teachers' competence and students' emotional quotient (R = 0, 5373 at the level of significance 5%o).Teachers' compelence gives a dominant contribution on biological learning achievment at 56, 4g%o. Teachers' compelence and students'emotional intelligence give effective contributions on biological learning achievment.at 28.8%.